Analysis of Ricebox Business Model in Bandung - Saanty, Debby Aulia; Aprilianty, Fitri (Journal of Innovation, Business and Entrepreneurship, 2019)
As a creative city, Bandung is also known as a culinary city because of the number of culinary product innovations it has, and ricebox is one example of a culinary phenomenon in Bandung. Nowadays, there many ricebox brands in Bandung, and its growth has begun to emerge. However, until now there has not been a proper business model to guide a Ricebox business in Bandung yet. In order to run the business well, Ricebox business in Bandung should create their own business model as their guidance on doing the business. This research is conducted to analyse the most suitable business model for ricebox in Bandung. The data collection is generated by doing the interview with 5 ricebox owners in Bandung and survey of 200 respondents. The result of the data is analysed by manual coding and descriptive statistic. The final result of this research is the recommendation for the most suitable business model for ricebox in Bandung. This research also aims to help PETJAH, as one of ricebox brands in Bandung to find the most suitable business model to be adopted.Keywords: Business Model, Customer Segments, Value Proposition, Ricebox